ANALISIS KEBUTUHAN BAHAN AJAR MATEMATIKA BERBASIS HOTS TERINTEGRASI AGAMA UNTUK SISWA MTS KELAS VII - Maretha Septiani Dwi Astutik; Syamsuri Syamsuri; Hepsi Nindiasari; Sukirwan Sukirwan (Jurnal Kajian Pembelajaran Matematika, 2021)
The purpose of this research is to analyze the need for developing HOTS-based mathematics teaching materials that are integrated with religion in MTs. The results of this research will later become the basis for developing religious-integrated HOTS teaching materials. The analysis stage refers to the Analyze stage in the ADDIE development model. The data collection technique was carried out by distributing questionnaires to 16 MTs mathematics teachers. This research shows that the majority of MTs mathematics teachers complain that the teaching materials are monotonous, less varied and not HOTS-based. The majority of mathematics learning that has been applied is with a scientific approach and applies 21st century learning. So far, when teaching mathematics, teachers use books, worksheets, modules, props and learning videos. Not all learning resources have been used by HOTS-based teachers. The majority of learning resources used by teachers have not been integrated with religion. The advantages of existing learning resources are that the material is complete, contextual, structured and uses a scientific approach. However, there are still shortcomings, including not being integrated with religious subjects due to the limitations of teachers regarding the knowledge of integrating mathematics subjects with material on religion, not implementing HOTS much and not being able to make students learn independently actively. From these results, it can be concluded that it is necessary to develop religious integrated HOTS- based mathematics teaching materials for MTs students.